Effect of Rosemary Transglutaminase on Yoghurt Fortified with Whey Protein Isolate - Ibrahim Osama; Glibowski Pawel; Nour Maher; El-Hofi Mahmoud; El-Tanboly El-Sayed; Abd-Rabou Nabil (Polish Journal of Food and Nutrition Sciences)
Rosemary (Rosmarinus officinalis L.) transglutaminase (RTGase) was used to cross-link whey protein isolate (WPI) and its ability to induce gelation was investigated. The rheological and textural properties of WPI were improved with RTGase treatment. Set-type yoghurts fortified with 1% WPI powder treated with RTGase at the level of 2.5 and 10 unit/g protein were studied. Chemical, rheological, textural and organoleptic properties of the yoghurt treated with RTGase were better than these of the control yoghurt.